Geostatistics and its potential in Agriculture 4.0 - Rodrigues, Marcos; Castrignanò, Annamaria; Belmonte, Antonella; Silva, Kátia; Lessa, Bruno (Revista Ciência Agronômica, 2021)
In order to meet future food demands and ensure sustainability new technologies have been incorporated into agriculture. Some researchers believe that we are living in the fourth agricultural revolution or Agriculture 4.0. Among the many technologies involved in the Agriculture 4.0, it is necessary to highlight the importance of geostatistics in the implementation of those technologies. Geostatistics is a class of statistics used to analyze and predict the values associated with spatial or spatiotemporal phenomena, and it is very important to understand the spatial distribution of agricultural variables. Therefore, the objective of this review is to show the potential of geostatistics in Agriculture 4.0. The article presents an exhaustive literature review of geostatistics and its potential in agriculture, by showing a brief of geostatistical approaches, some practical use of geostatistics in agriculture, and a description of multivariate geostatistics for multi-source data fusion using some case studies. This review showed that geostatistics has been used for agricultural purposes and has been producing exciting results. In addition, more advanced analysis such as multivariate geostatistics in fuse heterogeneous data can be easily adapted to any experimental conditions and type of sensor data and/or sampling data to increase estimation accuracy.